Pengaruh Pengekangan terhadap Beban Maksimum pada Benda Uji Kubus dan Silinder Menggunakan Metode Elemen Hingga - Fitriani Ridzeki (Jurnal Teknologi Berkelanjutan, 2021)
At the beginning of the Covid-19 pandemic and implementing Large-Scale Social Restrictions or PSBB, many structural laboratories also closed their activities. At the same time, some construction work still had to run. For construction services to continue to exist, it is necessary to adapt the information, technology,communication, and data management departments.The compressive strength test of concrete using confined cubes and cylinders has been carried out using the finite element method. The test object is a cube of 15 cm × 15 cm × 15 cm and a cube of 20 cm × 20 cm × 20 with 5 cm stirrups and a cylinder with a diameter of 15 cm and a height of 30 cm, which is restrained by a stirrup distance of 5 cm and 10 cm. One way to get reinforced concrete material that is sufficiently pliable is to provide confinement to the concrete. Confinement is the most effective solution in increasing the ductility (μ) and strain (εc) of concrete. So that the research carried out is testing the compressive strength of concrete on cubes and cylinders that are given restraints to get the maximum load value that occurs.The effect of restraint on the cube test object is the stirrup distance which affects the maximum load value, the closer the distance between the stirrups, the greater the maximum load value. Meanwhile, the cylindrical cross-section with square restraints does not affect the maximum load value.